Genetic Analysis of Drought Tolerance in Cowpea [Vigna Unguiculata (L.) Walp] - Olubunmi, D.I. (University Of Ghana, 2015)
Agriculture in Sub Saharan Africa (SSA) is under serious threat due to water shortage, population pressure and climate change. Cowpea, a protein-rich legume crop complements staple cereal and tuber crops in the diets of rural and urban people of the tropical and sub-tropical regions of the world. It therefore, plays a significant role in the sustainability of food and nutrition security in SSA. Cowpea, though reported to be inherently drought tolerant; but because it is mostly grown under rain-fed conditions towards the end of the rainy season in the drier parts of Nigeria, its productivity is still being adversely affected by the erratic pattern of rainfall which occurs frequently in these areas. Increasing the level of drought tolerance in existing cowpea varieties that will possess farmers’ preferred traits will increase farmers’ adoption of these varieties and ensure high and stable yield from farmers’ fields under the ever changing climatic conditions. The objectives of this study were therefore, to: (i) identify the impact of drought on cowpea production and farmers’ preferred traits in new cowpea varieties (ii) assess the diversity of cowpea germplasm for drought tolerance (iii) assess the combining ability of cowpea lines under drought and well-watered conditions and (iv) determine the gene action controlling drought tolerance in cowpea. The results of a Participatory Rural Appraisal (PRA) conducted in fifteen cowpea growing communities of Kano State, Nigeria established that drought, pests and diseases were major constraints to cowpea production. Drought reduced grain yield and fodder yield to about 62% and 56% of realizable yield under normal condition respectively. Fifty-eight percent of the farmers confirmed drought at the flowering / pod-filling stage was more devastating than drought occurring at the vegetative stage (32%) while 10% of the farmers confirmed that both growth stages were both growth stages are susceptible to University of Ghana http drought. Consumer-based traits such as large seed, short cooking time and dual-purpose varieties which increase farmers’ income were identified as important preferred traits as well as traits for biotic and abiotic tolerances in new cowpea varieties. Ninety-one cowpea varieties were screened for tolerance to drought using the wooden box screening technique with the aim to identify parents to be used for genetic analysis studies. Twenty lines were selected based on their responses to the screening and were mated in a North Carolina Design II to generate 100 single F1 crosses. The F1 progenies and their parents were evaluated under drought and well-watered conditions at two locations. Grain yield of the F1 progenies ranged between 2533 kg ha-1 for TVu6707 x TVu9797 and 18 kg ha-1 for TVu11986 x TVu2736 under drought stress, 3786 kg ha-1 for TVu6707 x TVu9797 and 45 kg ha-1 for TVu633 x TVu2736 under well-watered conditions. General Combining Ability (GCA) and Specific Combining Ability (SCA) mean squares were significant for grain yield and other traits across all research environments indicating that both additive and non-additive gene effects were important in the control of grain yield and other drought adaptive traits across all research environments. The contribution of GCA (71%) to the total sum of squares was higher than that of SCA (21%) for grain yield under drought stress indicating that additive gene action was more important in the inheritance of grain yield under drought stress. Similarly, the superior positive GCA (GCA-female and GCA-male) effects for 100-seed weight, number of seeds per pod, Normalized Difference Vegetation Index (NDVI) measured at three different growth stages, the number of pods and seeds per plant under drought stress indicated that additive gene action was more important in the inheritance of these yield related traits under drought stress. The lines TVu79, TVu6707, TVu9693 and TVu9707 were identified as general good combiners with outstanding. positive GCA effects for grain yield under drought stress. These can be used as parents to generate improved cowpea varieties for drought tolerance. Considering both mean yield and stability performance, TVu8670 x Sanzi, IT89D-288 x TVu8670, TVu6707 x TVu79 and TVu8670 x TVu79 can further be advanced for development of novel drought tolerant varieties.
Thesis(Phd)-University Of Ghana,2015
Keywords: Genetic; Drought; Cowpea [Vigna Unguiculata (L.) Walp]